(untitled) - Applegate, Katherine; Santoso, Charles (Feiwel and Friends, 2021)
When the annual migration of hummingbears, a source of local pride and income, dwindles and no one knows why, Willodeen, armed with a magical birthday gift, speaks up for the animals she loves and vows to uncover this mystery.
Keywords: Nature; Juvenile fiction; Ecology; Juvenile fiction; Nature; Fiction; Ecology; Fiction; Fantasy fiction